MERDEKA DALAM PEMBELAJARAN - Samsul Bahri; Herman Herman; Moh Shaleh; Marzuki Marzuki (Pascasarjana IAIN Sultan Amai Gorontalo, 2021)
This paper proves that the fundamental problem in learning is to use a bank-style teaching model that castrates the creative potential of students and leads to authoritarian feudalistic teaching. The method used is analytical descriptive with the approach of social history and education science. The result is that independence in learning by using learning models is the choice of teachers because this model can build and liberate students' creativity, even with this model education can develop the mission of humanizing humans, and can print generations of quality both scientifically and morally.